The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/14616734.2013.782650
|View full text |Cite
|
Sign up to set email alerts
|

Parent-specific reciprocity from infancy to adolescence shapes children's social competence and dialogical skills

Abstract: Reciprocity - the capacity to engage in social exchange that integrates inputs from multiple partners into a unified social event - is a cornerstone of adaptive social life that is learned within dyad-specific attachments during an early period of neuroplasticity. Yet, very little research traced the expression of children's reciprocity with their mother and father in relation to long-term outcomes. Guided by evolutionary models, we followed mothers, fathers, and their firstborn child longitudinally and observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
114
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 57 publications
8
114
0
5
Order By: Relevance
“…Fonagy, Gergely, Jurist, and Target (2002) suggested that the evolutionary function of the dyadic relationship between parent and human infant goes far beyond ensuring the safety of the latter, to furthering the understanding of the nature of subjectivity and the ability to develop social intelligence, skills, and competence (e.g., Feldman, Bamberger, & Kanat-Maymon, 2013). Indeed, our results provide preliminary evidence that the infant's experience of the mother's embodied mentalizing carries over into childhood and expands beyond the parent-infant relationship, seeming to influence (in this observational study) the development of social skills as late as 54 months.…”
Section: Discussionmentioning
confidence: 99%
“…Fonagy, Gergely, Jurist, and Target (2002) suggested that the evolutionary function of the dyadic relationship between parent and human infant goes far beyond ensuring the safety of the latter, to furthering the understanding of the nature of subjectivity and the ability to develop social intelligence, skills, and competence (e.g., Feldman, Bamberger, & Kanat-Maymon, 2013). Indeed, our results provide preliminary evidence that the infant's experience of the mother's embodied mentalizing carries over into childhood and expands beyond the parent-infant relationship, seeming to influence (in this observational study) the development of social skills as late as 54 months.…”
Section: Discussionmentioning
confidence: 99%
“…Although humans are among the few mammalian species where some male parental caregiving is relatively common, father involvement varies considerably within and across cultures, adapting to ecological conditions (1,3). Involved fathering has been linked with children's long-term physiological and social development and with increases in mothers' caregivingrelated hormones such as oxytocin and prolactin (3)(4)(5)(6). In addition, animal studies demonstrated structural brain alterations in caregiving fathers (7,8).…”
mentioning
confidence: 99%
“…It has been suggested that, although maternal caregiving is triggered by neurobiological processes related to pregnancy and labor, the human father's brain, similar to other biparental mammals, adapts to the parental role through active involvement in childcare (1)(2)(3). Despite growing childcare involvement of fathers (3,5,6), mechanisms for human fathers' brain adaptation to caregiving experiences remain largely unknown, and no study to our knowledge has examined the brain basis of human fatherhood when fathers assume primary responsibility for infant care.…”
mentioning
confidence: 99%
“…First, fathers overall are increasingly involved in childrearing (Pleck & Masciadrelli, 2004). Second, whether a child is among the approximately 64% of children (including children with ASD) in the United States who reside in a two-parent household (Freedman, Kalb, Zablotsky, & Stuart, 2012), or is in a home with a nonresident father, high-quality paternal involvement with children is related to improved child outcomes, accounting for variance beyond that accounted for by mother-child relationship variables (e.g., Adamsons & Johnson, 2013;Feldman, Bamberger, & Kanat-Maymon, 2013;Washington et al, 2014). The generalizability of these findings for fathers of typically developing children to fathers of children with ASD is unknown at this time.…”
mentioning
confidence: 99%